Comparison Period Fertility in 2001 and 2011 - Devkota, Bijaya Mani (Rural Development Journal, 2017)
Indirect demographic techniques have proven to be useful tools in the developing world, as their application to census and survey data has greatly expanded knowledge of the demographic situation in data deficient countries (Brass, 1996). The different techniques are based on specific assumptions and robustness of available data thus deserves caution in application. Failure to adhere to these methodological specifications results in generation of more errors (Feeney, 1996). The impetus of this paper is to assess the applicability of various methods in estimating recent fertility levels in Nepal. It obtains optimal fertility estimates, the research undertook extensive data assessment, and corrections where possible, of individual variables employed hypothetical inter survey cohort method. In line with previous studies, the magnitude and pattern of the hypothetical inter survey method represented strong evidence of fertility decline in Nepal. This evidence rendered the Hypothetical inter-survey cohort appropriate for estimation of the fertility level in the country for the period. The study undertook and presented detailed data evaluation and adjustments, adhering to the Arriaga method and changing P/F ratio methodological assumptions. Hence, serious prudence should be taken during data collection and processing in order to minimise the magnitude of the errors. Hypothetical inter -survey cohort also support estimation of TFR values is 3.171 in between 2001-2011.